A Cobalt‐Modified Covalent Triazine‐Based Framework as an Efficient Cocatalyst for Visible‐Light‐Driven Photocatalytic CO2 Reduction. Issue 8 (23rd August 2019) - Bi, Jinhong; Xu, Bin; Sun, Long; Huang, Huimin; Fang, Shengqiong; Li, Liuyi; Wu, Ling
Abstract: Photocatalytic CO2 reduction into carbonaceous feedstock chemicals is a promising renewable energy technology to convert solar energy and greenhouse gases into chemical fuels. Here, a covalent triazine‐based framework (CTF) is demonstrated as an efficient cocatalyst to reduce CO2 under visible‐light irradiation. The nitrogen‐rich triazine moieties in CTF contribute to CO2 adsorption, while the periodical pore structure of CTF favors the accommodation of CO2 and electron mediator. Immobilization of cobalt species onto CTF promotes the photocatalytic activity with a 44‐fold enhancement over pristine CTF and the optimal CO production rate of the obtained Co/CTFs was up to 50 μmol g −1 h −1 . The results of solid‐state UV‐vis diffuse reflectance spectra (UV‐vis DRS), CO2 adsorption and electrochemical impedance spectroscopy (EIS) illustrated that the increased activity was ascribed to the enhanced CO2 capture capacity, improved absorption of visible‐light and facilitated the transfer of charge from CTF to CO2 molecules. The CTF not only serves as a substrate for active Co species, but also bridges the photosensitizer with cobalt catalytic sites for the efficient transfer of photoexcited electrons. This work highlights the capability and ease of fabricating covalent organic framework‐based photocatalytic systems that are potentially useful for energy‐conversion applications. Abstract : Light it up : An efficient approach to improve the photocatalytic activity for CO2 reduction under visible light irradiation by using cobalt‐modified covalent triazine frameworks was proposed. The resulted Co/CTF‐1 greatly enhanced the visible‐light‐driven photocatalytic properties for the reduction of CO2 compared to pristine CTF and Co3 O4 . The optimal CO production rate of the obtained Co/CTFs was up to 50 μmol g −1 h −1, owing to the enhanced adsorption of visible‐light, improved CO2 capture capacity and efficient separation of electron‐hole pairs.